The laboratory diagnosis of Chlamydia trachomatis infections - Max A Chernesky (Canadian Journal of Infectious Diseases and Medical Microbiology)
Lower genital tract infections with Chlamydia trachomatis are predominantly asymptomatic in men and women. Diagnostic technology has provided several approaches to the diagnosis of C trachomatis. Outside of cells, Chlamydia can die or degrade without optimal storage and transportation. Because some of the other assays perform better on certain specimen types, it is important for laboratories to recognize these differences and provide advice to physicians and nurses collecting patient specimens, with the objective of diagnosing lower genital tract infections to prevent transmission and upper tract damage. Most invasive specimens, such as cervical or urethral swabs, may be collected for culture, antigen or nucleic acid detection. Noninvasive samples such as first-void urine and vaginal swabs can be easily collected by the patient; these samples must be tested by more sensitive nucleic acid amplification tests. These newer investigative strategies should enable implementation of screening programs to identify and treat partners. Serology has not been particularly useful for the diagnosis of acute C trachomatis infections in adults. Presently, it appears that antibiotic-resistant C trachomatis is not a clinical problem. Laboratories providing C trachomatis diagnosis require participation in continuous quality improvement programs.